Destination foods image and intention to visit - Adibah Md Samsuday; Karam Kaur Prem Singh; Lee Jin Long; Mohamad Izzatullah Hamid (2016)
In recent year, tourism having lots of event which has marked change in Malaysia. Foods event become popular among the local people and international people. The growth of foods event can be described as the growth of the people who came to the event. The positive acceptance from the tourists encouraged many international people to visit Malaysia. This research has been conducted to identify the intention of tourist to come at a destination. A set of questionnaire has been use as a collecting data method and distributed to 384 respondents among tourist who attend the foods event. The data was analyzed by using Statistical Packages for Special Science (SPSS) software version 24.0.0.0. As an overall finding, the survey found that tourist love to come at the foods event. As a conclusion, the foods event give a high influence towards tourist.